Manajemen Pembelajaran PAUD dengan Pendekatan Senta di TK Aisyiyah Beran - Baniyatun, Marlina; Purbonuswanto, Welius (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to describe (1) ECCE learning management in Aisyiyah Beran Kindergarten (2) To find supporting factors, obstacles and solutions about ECCE learning management with a central approach in Aisyiyah Beran Kindergarten.This research uses a qualitative approach with a descriptive type. The sources of research data were the principal, 3 class teachers and 3 guardians. Data collection techniques use in-depth interviews, observation, and documentation techniques. Data analysis techniques using the Miles and Huberman model are data reduction, data display, and conclusion. Test the validity of the data using triangulation and source triangulation techniques.The results showed that (1) PAUD learning management in Aisyiyah Beran Kindergarten includes: a) Learning program planning and institutional development programs; b) The organization of the institution is made based on the main duties and functions of each member; c) Drive the Institute's program based on plans that have been made and implemented; d) Control at the Institute is carried out internally by the principal. Meanwhile, external supervision is carried out by the Aisyiyah Foundation, a kindergarten supervisor from the Korwil Dinas Pendidikan dan Institutional Accreditation. The implementation of the learning center approach in Aisyiyah Beran Kindergarten has 4 types, namely the preparation center, nature center, beam center and acting and body processing center. (2) supporting and inhibiting factors in the implementation of learning come from teachers and schools (3) efforts made by teachers in overcoming obstacles are to increase teacher creativity.